Density and entropy of immune cells within the tumor microenvironment of primary tumors and matched brain metastases - Kleinberger, Markus; Cifci, Didem; Paiato, Christina; Tomasich, Erwin; Mair, Maximilian; Steindl, Ariane; Spiró, Zoltán Péter; Carrero, Zunamys I.; Berchtold, Luzia; Hainfellner, Johannes A.; Müllauer, Leonhard; Heller, Gerwin; et al. (Acta Neuropathologica Communications, 2025)
Tumor-infiltrating lymphocytes (TILs) and tumor-associated macrophages (TAMs) have increasingly been reported to impact the brain metastatic process of solid tumors. However, data on intra-individual differences between primary tumor and brain metastasis (BM), as well as their correlation with clinical outcome parameters, is scarce.